Strain-engineered graphene grown on hexagonal boron nitride by molecular beam epitaxy - Summerfield, Alex; Davies, Andrew; Cheng, Tin S.; Korolkov, Vladimir V.; Cho, YongJin; Mellor, Christopher J.; Foxon, C. Thomas; Khlobystov, Andrei N.; Watanabe, Kenji; Taniguchi, Takashi; Eaves, Laurence; Novikov, Sergei V.; et al. (Nature Publishing Group, 2016)
Graphene grown by high temperature molecular beam epitaxy on hexagonal boron nitride (hBN) forms continuous domains with dimensions of order 20 μm, and exhibits moiré patterns with large periodicities, up to ~30 nm, indicating that the layers are highly strained. Topological defects in the moiré patterns are observed and attributed to the relaxation of graphene islands which nucleate at different sites and subsequently coalesce. In addition, cracks are formed leading to strain relaxation, highly anisotropic strain fields, and abrupt boundaries between regions with different moiré periods. These cracks can also be formed by modification of the layers with a local probe resulting in the contraction and physical displacement of graphene layers. The Raman spectra of regions with a large moiré period reveal split and shifted G and 2D peaks confirming the presence of strain. Our work demonstrates a new approach to the growth of epitaxial graphene and a means of generating and modifying strain in graphene.